2021
DOI: 10.1002/ldr.4093
|View full text |Cite
|
Sign up to set email alerts
|

Estimating land use/land cover change impacts on vegetation response to drought under ‘Grain for Green’ in the Loess Plateau

Abstract: A series of serious environmental problems have appeared in North China, especially in the Loess Plateau. The 'Grain for Green Program' project has been implemented to address issues caused by vegetation degradation. Human beings play a key moderating role between drought and vegetation; however, it is not clearly understood how typical land cover changes from human activities impact the ability of vegetation to resist drought. To represent meteorological drought and vegetation dynamics, this study applied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In addition, variability in NBE due to land use change may also be a source of uncertainty. Land use changes that alter GPP should also impact SIF (e.g., del Rosario Uribe & Dukes, 2021; Ding et al., 2021) and should therefore be accounted for in model simulations. Land use changes that unfold over decades will undoubtedly change biome‐level patterns in NBE but may not be detectable across the relatively short, 4‐year duration of this study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, variability in NBE due to land use change may also be a source of uncertainty. Land use changes that alter GPP should also impact SIF (e.g., del Rosario Uribe & Dukes, 2021; Ding et al., 2021) and should therefore be accounted for in model simulations. Land use changes that unfold over decades will undoubtedly change biome‐level patterns in NBE but may not be detectable across the relatively short, 4‐year duration of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (2020) showed that the increasing ET in the LP was mainly driven by the ongoing optimization of human land-use management that was closely related to socio-economic development. Studies in the LP also found that the land use/land cover changes caused by the Grain for Green project modulated both surface humidity (Zhang et al, 2018) and vegetation responses to drought (Ding et al, 2021).…”
Section: Growth Period-specific Spatiotemporal Dynamics Of Dsimentioning
confidence: 99%
“…Revegetation is generally considered to be an effective way to restore fragile ecosystems by increasing the leaf area of vegetation, enhancing carbon sequestration and improving vegetation service functions (Chen et al, 2019; Cui et al, 2020; Ding et al, 2021; Liu et al, 2008). In China, the 16,000 km 2 of revegetation was implemented by the Grain‐for‐Green Program (GFG), which focuses on soil erosion control over the Chinese Loess Plateau (CLP) region (Feng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Revegetation is generally considered to be an effective way to restore fragile ecosystems by increasing the leaf area of vegetation, enhancing carbon sequestration and improving vegetation service functions (Chen et al, 2019;Cui et al, 2020;Ding et al, 2021;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%